2012
DOI: 10.1111/j.1442-200x.2012.03648.x
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin status associated with performance IQ but not verbal IQ in Chinese preschool children

Abstract: Background Despite the body of literature that links anemia with poorer cognition in children and the evidence that the severity of the effects of anemia on children’s cognition vary in different populations, few studies have investigated the effects of anemia on the cognitive development of Chinese children. Study Design This longitudinal cohort includes 171 children from a developing region of China. Hemoglobin and iron levels were taken when the children were 4 years old. At age 6, the children’s cognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 47 publications
3
26
1
Order By: Relevance
“…These studies have focused on cognitive scores or educational achievement, with only one assessing motor (Kuklina et al, 2006) and none assessing social-emotional development. Although several studies have examined relationships of Hb concentration during early life with long-term developmental outcomes (Ai, Zhao, Zhou, Ma, & Liu, 2012;Aubuchon-Endsley et al, 2011;Aubuchon-Endsley et al, 2013;Eilander et al, 2010;Grantham-Mcgregor & Ani, 2001;Jianghong, Adrian, Venables, & Mednick, 2004;Olney et al, 2009;Su et al, 2016), only one study to our knowledge reported independent associations with Hb during specific periods of childhood by adjusting for Hb at other time points (Aubuchon-Endsley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have focused on cognitive scores or educational achievement, with only one assessing motor (Kuklina et al, 2006) and none assessing social-emotional development. Although several studies have examined relationships of Hb concentration during early life with long-term developmental outcomes (Ai, Zhao, Zhou, Ma, & Liu, 2012;Aubuchon-Endsley et al, 2011;Aubuchon-Endsley et al, 2013;Eilander et al, 2010;Grantham-Mcgregor & Ani, 2001;Jianghong, Adrian, Venables, & Mednick, 2004;Olney et al, 2009;Su et al, 2016), only one study to our knowledge reported independent associations with Hb during specific periods of childhood by adjusting for Hb at other time points (Aubuchon-Endsley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ai et al . found a significant correlation between Hb concentration at 48 months and verbal IQ ( r = 0.14, P < 0.05) and performance IQ ( r = 0.08, P < 0.05) at 72 months of age in Chinese children . In Icelandic children with 7.2% anemia prevalence, a significant association was reported between Hb at 12 months and expressive language development at 72 months of age …”
Section: Resultsmentioning
confidence: 83%
“…Many studies did not report the participation rate; of those that did, five studies reported a participation rate above 80% and three reported a participation rate between 60% and 80% . In only two studies was it unclear how the subsample of participants was selected . Some longitudinal studies had a loss to follow‐up above 20% .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with this theory, a longitudinal cohort study by Ai et al in 171 children in China showed that children with low hemoglobin levels had a lower performance IQ, but normal verbal IQ. 17 Nitric oxide controls the transmission of information and plays a role in cognitive function, such as in learning and memory, so that NO deficiency may cause cognitive impairment. We found no correlation between verbal IQ or full scale IQ and serum NO levels.…”
Section: Discussionmentioning
confidence: 99%